Consistency of triage scores by presenting complaint pre‐ and post‐implementation of a real‐time electronic triage decision support tool - Shelley L. McLeod; Cameron Thompson; Bjug Borgundvaag; Lehana Thabane; Howard Ovens; Steve Scott; Tamer Ahmed; Keerat Grewal; Joy McCarron; Brooke Filsinger; Nicole Mittmann; Andrew Worster; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objective eCTAS is a real‐time electronic decision‐support tool designed to standardize the application of the Canadian Triage and Acuity Scale (CTAS). This study addresses the variability of CTAS score distributions across institutions pre‐ and post‐eCTAS implementation. Methods We used population‐based administrative data from 2016–2018 from all emergency departments (EDs) that had implemented eCTAS for 9 months. Following a 3‐month stabilization period, we compared 6 months post‐eCTAS data to the same 6 months the previous year (pre‐eCTAS). We included triage encounters of adult (≥17 years) patients who presented with 1 of 16 pre‐specified, high‐volume complaints. For each ED, consistency was calculated as the absolute difference in CTAS distribution compared to the average of all included EDs for each presenting complaint. Pre‐eCTAS and post‐eCTAS change scores were compared using a paired‐samples t‐test. We also assessed if eCTAS modifiers were associated with triage consistency. Results There were 363,214 (183,231 pre‐eCTAS, 179,983 post‐eCTAS) triage encounters included from 35 EDs. Triage scores were more consistent (P < 0.05) post‐eCTAS for 6 (37.5%) presenting complaints: chest pain (cardiac features), extremity weakness/symptoms of cerebrovascular accident, fever, shortness of breath, syncope, and hyperglycemia. Triage consistency was similar pre‐ and post‐eCTAS for altered level of consciousness, anxiety/situational crisis, confusion, depression/suicidal/deliberate self‐harm, general weakness, head injury, palpitations, seizure, substance misuse/intoxication, and vertigo. Use of eCTAS modifiers was associated with increased triage consistency. Conclusions eCTAS increased triage consistency across many, but not all, high‐volume presenting complaints. Modifier use was associated with increased triage consistency, particularly for non‐specific complaints such as fever and general weakness.